P02.14 Tumour Treating Fields (TTFields) demonstrate variable efficacy on high-grade paediatric brain tumour cell lines in a frequency-dependent manner. (19th September 2018) - Branter, J; Estevez Cebrero, M; Grundy, R; Basu, S; Smith, S
Abstract: Background: The EF-14 trial of the Optune system which utilises Tumour Treating Fields (TTFields) to disrupt dividing cells has shown survival benefit in adult Glioblastoma multiforme (GBM) patients. These results have given credence to the addition of alternating electric fields to existing conventional therapy regimes for brain tumour patients. Here we present data showing how TTFields may inhibit division of our paediatric GBM, Medulloblastoma and Ependymoma cell lines. Material and Methods: We delivered TTFields over a range of clinically relevant frequencies (100-400kHz) to our panel of high grade paediatric cell lines using the Inovitro system. The effects of TTFields on cell viability was assessed using metabolic tests and cell count, and cell cycle analysis was performed using flow cytometry. TTFields was combined with paclitaxel and cell viability was measured to assess efficacy of the combinational approach. Gene expression analysis following TTFields treatment was performed via Affymetrix microarray. Results: TTFields have significant efficacy on all of our cell lines in a frequency-dependent manner. Cells treated with TTFields exhibited up to 75% slower growth rates when re-seeded and compared to untreated cells. Cell cycle analysis revealed that TTFields treated cells have significant accumulation in the G2/M phase relative to control cells. The efficacy of TTFields may be significantly increased with the addition of the paclitaxel. The effects of TTFields treatment on gene expression will be discussed. Conclusion: TTFields treatment has shown significant efficacy against our panel of paediatric GBM, Medulloblastoma and Ependymoma cell lines. The optimal frequencies determined for some of our cell lines fall outside the 200KHz range used in the clinic for adult GBM patients.